Rhetorics as a Means to Persuade in Public Service Announcements on Mental Health - Nadia Husna, Yusuf Anthony; Rosnah, Mustafa (UNIMAS Publisher, 2023)
Advertisements target the beliefs and expectations of customers for persuasive advantage using rhetorical logic. The word “advertisement” usually conjures images of product promotions. However, advertisements are not only used by professional business owners to sell a product but also to share ideas, highlight information and increase awareness. This type of advertisement is called Public Service Advertisements (PSAs). In PSAs, the intention is not commercial gains, but to educate the public on certain issues such as health, hygiene, and environmental issues, to name a few. PSAs publicise the service of government agencies and non-governmental organisations in areas such as disability support services, emergency preparedness, and anti-smoking. The PSAs can take the form of digital advertisements and physical advertising. Digital advertising involves advertising through the usage of technology, for example, social media, television, or radio broadcast. Physical advertising involves traditional press advertising (e.g., newspapers, magazines, flyers), mobile billboard advertising, in-store advertising, coffee cup advertising, as well as outdoor or street advertising.